Karakterisasi Sifat Termal dan Mekanik Material Komposit Serat Alam sebagai Material Ramah Lingkungan - Kemal Fahrizi Azch; Kholil Abdul Karim; Mhd Hamdani (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Natural fiber based composite materials are increasingly being developed as an environmentally friendly alternative to synthetic fiber-based composites. This study aims to characterize the thermal and mechanical properties of natural fiber composite materials and evaluate their potential use as sustainable materials. Composites are made using natural fibers as reinforcement and a polymer matrix through a specific molding method. Mechanical property characterization includes tensile tests, flexural tests, and impact tests, while thermal property characterization is carried out using thermal analysis to determine the thermal stability of the material. The test results show that the addition of natural fibers has a significant effect on improving the mechanical properties of the composite, especially tensile strength and elastic modulus, compared to the unreinforced matrix. In addition, natural fiber composites show quite good thermal stability over a certain temperature range, making them suitable for non-structural applications. Based on these results, natural fiber composite materials have the potential to be developed as environmentally friendly materials that have competitive mechanical and thermal performance.